A soybean meal-based wood adhesive improved by a diethylene glycol diglycidyl ether: properties and performance. Issue 78 (4th August 2016) - Yuan, Cheng; Luo, Jing; Luo, Jianlin; Gao, Qiang; Li, Jianzhang
Abstract : A soybean meal was used to make an effective, biodegradable adhesive for plywood applications using the long-chain crosslinker diethylene glycol diglycidyl ether (DGDE) and the denaturation agent sodium dodecyl sulfate (SDS). Abstract : A soybean meal was used to make an effective, biodegradable adhesive for plywood applications using the long-chain crosslinker diethylene glycol diglycidyl ether (DGDE) and the denaturation agent sodium dodecyl sulfate (SDS). The residual rate, functional groups, and morphological properties of the adhesive were investigated to explain the effect of DGDE on the properties and performance of the resultant adhesives. Three-ply plywood was fabricated with the resulting adhesive, and its wet shear strength was measured. The results showed that the water resistance of the adhesive with 8 g of DGDE improved by 16.8% compared to that without DGDE, and the wet shear strength of plywood bonded by the adhesive reached 1.04 MPa, meeting the interior use panel water resistance requirement. This improvement was attributed to the following: ① incorporating DGDE into the adhesive formed a dense cross-linking structure due to chemical reactions between DGDE and active groups on the protein molecules, improving the water resistance of the cured adhesive. ② Adding DGDE decreased the adhesive viscosity and increased the solid content, which increased the amount of the adhesive that penetrated the wood's surface and formed more interlocks. ③ DGDE addition increased the toughness of the adhesive, which greatly improved the impact resistance of the adhesive and decreased the interior force of the resulting plywood. ④ Using DGDE promoted a smooth and homogeneous fracture surface of the cured adhesive, which effectively prevented water intrusion and improved water resistance. The modified adhesive proved practical as a plywood adhesive for industrial use.